Markets and market boundaries: a social practice approach. Issue 2 (13th March 2017) - Gosling, Martyn; Richard, James; Seo, Yuri
Abstract : Purpose: The paper contributes to the debate on a general theory of markets. The purpose of this paper is to develop a market practice model based on social practice theories, and explore new ways of describing market boundaries. Design/methodology/approach: A conceptual analysis of contemporary marketing directions and market theorizations provides a basis for defining markets and market boundaries in terms of social practices and their performances by market actors. Findings: Based on the market performances held in place by institutional practices that define, contextualize and stabilize a market, this paper defines market boundaries by nine specific categories of practices, described here as parameters. Research limitations/implications: This is a conceptual paper. Future research using empirical evidence derived from situated investigations should endeavor to refine the model and practices that define market boundaries. Originality/value: The paper provides a new conceptualization of markets and market boundaries from the social practice perspective, and advances contemporary market theorizing that puts services at the center of exchange. The paper offers managerial implications by describing alternative means for analyzing markets and developing corresponding competitive strategies. Furthermore, the conception of market boundaries as nine parameters provides insights beyond the geographic and price boundaries typically used to describe market limits and exchange processes when developing policy.